Coral-Associated Bacteria Provide Alternative Nitrogen Source for Symbiodiniaceae Growth in Oligotrophic Environment - Yawen Liu; Yanying Hua; Yan Yi; Jicai Liu; Pengcheng Fu (Microorganisms)
Coral reefs thrive in nutrients-poor waters, and their survival strategy in such oligotrophic marine environments remains largely unexplored. Current coral research has focused on the interplay between the animal hosts, symbiotic Symbiodiniaceae, and associated bacteria, with little attention given to their individual interactions. Here, we integrated biochemical, transcriptomic, and metabonomic analyses of the clade D Symbiodiniaceae strain AG11 to investigate the growth-assisting mechanisms of symbiotic bacteria. Our findings indicate that metabolic trophallaxis between Symbiodiniaceae and symbiotic bacteria plays a crucial role in enhancing survival and population growth under nitrogen-depleted conditions, commonly found in typical coral habitats. Notably, the exchange of organic compounds between Symbiodiniaceae and bacteria significantly boosts nitrogen uptake in their free-living state. Furthermore, we demonstrated how beneficial bacteria influence the survival of Symbiodiniaceae in response to environmental changes, which are vital for coping with nitrogen-depleted conditions where coral reefs are particularly vulnerable.